2019
DOI: 10.1002/adma.201901673
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Low‐Dimensional Ruddlesden–Popper Perovskite Solar Cells with over 17% Power Conversion Efficiency and Improved Stability

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adma.201901673.Low-dimensional Ruddlesden-Popper perovskites (RPPs) exhibit excellent stability in comparison with 3D perovskites; however, the relatively low power conversion efficiency (PCE) limits their future application. In this work, a new fluorine-substituted phenylethlammonium (PEA) cation is developed as a spacer to fabricate quasi-2D (4FPEA) 2 (MA) 4 Pb 5 I 16 (n = 5) perovskite solar cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
290
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(298 citation statements)
references
References 40 publications
5
290
3
Order By: Relevance
“…As shown in Figure 1b, the three cutting methods along the 〈100〉, 〈110〉, and 〈111〉 crystal directions will form three 2D perovskites with the structural formulas A′ 2 A n−1 B n X 3n+1 , A 2 A′ m B m X 3m+2 , and A′ 2 A q−1 B q X 3q+3 , respectively. Among them, the shearing method along the 〈100〉 crystal direction is the most common, and it can form three 2D perovskite phases, Ruddlesedn-Popper (R-P) [53,54] Dion-Jacobson (D-J) [55][56][57] and alternating cations in the interlayer space (ACI). [58][59][60] Their structures are illustrated in Figure 2a.…”
Section: Crystal Structurementioning
confidence: 99%
“…As shown in Figure 1b, the three cutting methods along the 〈100〉, 〈110〉, and 〈111〉 crystal directions will form three 2D perovskites with the structural formulas A′ 2 A n−1 B n X 3n+1 , A 2 A′ m B m X 3m+2 , and A′ 2 A q−1 B q X 3q+3 , respectively. Among them, the shearing method along the 〈100〉 crystal direction is the most common, and it can form three 2D perovskite phases, Ruddlesedn-Popper (R-P) [53,54] Dion-Jacobson (D-J) [55][56][57] and alternating cations in the interlayer space (ACI). [58][59][60] Their structures are illustrated in Figure 2a.…”
Section: Crystal Structurementioning
confidence: 99%
“…[ 10,11 ] In addition, through rational design of organic spacer cations with highly conductive conjugated spacers, it was found that the enhanced interplane coupling in 2D perovskites could efficiently promote charge transport. [ 12–14 ] However, RPP films with large n values exhibit more features like their 3D counterparts and a trade‐off between the PCE and stability has to be made in such case. [ 10,15 ]…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] These 2D PVKs can still be solution-processed and uniquely come with the quantum well structure formed by lead halide layers separated by hydrophobic organic cation spacer layers. [19][20][21][22] These 2D PVKs can still be solution-processed and uniquely come with the quantum well structure formed by lead halide layers separated by hydrophobic organic cation spacer layers.…”
mentioning
confidence: 99%